The Influence of Organizational Culture on Service Quality at Medan Satria Police Station - Sumarjono; Agus Cholik; Cendira, Lezildan (Lead Journal of Economy and Administration, 2024)
This study examines the influence of organizational culture on service quality at the Medan Satria Police from the perspective of the community as service recipients. Using a quantitative approach, the study was conducted using a survey method on 100 community respondents who had used the Medan Satria Police services. Data collection used a questionnaire with a Likert scale that measured community perceptions of seven dimensions of organizational culture and five dimensions of service quality. Data analysis using simple linear regression showed that organizational culture has a positive and significant influence on service quality with a coefficient of determination (R²) of 0.685. The service orientation dimension provides the largest contribution (32.4%) to improving service quality. The research results indicate the importance of strengthening the implementation of organizational cultural values that are oriented towards community satisfaction through innovative programs and the development of service competencies.